The Abundance of Phytoplankton in Peat Ponds of Patin Fish (Pangasius sp.) Given Biofertilizer Mixture - Marthalena Agustini Sihite; Syafriadiman Syafriadiman; Saberina Hasibuan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract This research was conducted from October to December 2019 in the Peatlands of Kualu Nenas Village, Tambang District, Kampar Regency, Riau Province, at the Aquaculture Environmental Quality Laboratory of the Fisheries and Maritime Faculty and the Marine Biology Chemistry Laboratory of the Fisheries and Maritime Faculty, Riau University. The purpose of this study was to improve the effect of adding a mixture of human faecal biofertilizer and cow faecal biofertilizer in increasing phytoplankton abundance, growth and survival of catfish in peat ponds. This research method is an experimental method, a Completely Randomized Design (CRD) using 1 factor (biofertilizer mixture) and 5 treatment stages (P0: without giving biofertilizer mixture; P1: giving 20% human feces biofertilizer mixture + 80% bovine feces; P2: giving biofertilizer mixture 40% human feces + 60% cow feces; P3: administration of biofertilizer mixture 60% human feces + 40% cow feces and P4: administration of biofertilizer mixture 80% human feces + 20% cow feces) with 3 replications. The results of this study showed that P4 (giving 80% human feces + 20% cow feces biofertilizer mixture) was the best treatment to increase the abundance of phytoplankton (48,435 ind/L), weight weight (17.30 gram), absolute length (4.40 cm) and survival of catfish (86%) compared to other treatments. Also showed the parameters of water quality in accordance with the survival of catfish. The water quality parameter values at P4 are temperature (26-29oC), ppH (6-7), DO (4.2-6.0 mg/L), free CO2(32.71-26.10 mg/L) , nitrate (3.05 mg/L) and orthoposphate (4.12 mg/L). Keyword: Peat Soil, Biofertilizer Mixture, Phytoplankton, Catfish